2017
DOI: 10.1016/j.nima.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Capacitively coupled pickup in MCP-based photodetectors using a conductive metallic anode

Abstract: We have designed and tested a robust 20 × 20 cm 2 thin metal film internal anode capacitively coupled to an external array of signal pads or micro-strips for use in fast microchannel plate photodetectors. The internal anode, in this case a 10nm-thick NiCr film deposited on a 96% pure Al 2 O 3 3mm-thick ceramic plate and connected to HV ground, provides the return path for the electron cascade charge. The multi-channel pickup array consists of a printed-circuit card or glass plate with metal signal pickups on o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Capacitively-coupled MCP-PMT anodes have been implemented using resistive thick films or semi-conductors [78,79,80,81,82,83,84], and MCP-PMTs with resistive capacitivelycoupled anodes are commercially available [80,85]. During this thesis work, it was demonstrated that a thin-metal layer made of NiCr can also transmit the high-frequency components of MCP-PMT pulses to an external array of electrodes, provided that the resistance is greater than about 1 kΩ per square [58].…”
Section: Capacitively-coupled Pickupmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacitively-coupled MCP-PMT anodes have been implemented using resistive thick films or semi-conductors [78,79,80,81,82,83,84], and MCP-PMTs with resistive capacitivelycoupled anodes are commercially available [80,85]. During this thesis work, it was demonstrated that a thin-metal layer made of NiCr can also transmit the high-frequency components of MCP-PMT pulses to an external array of electrodes, provided that the resistance is greater than about 1 kΩ per square [58].…”
Section: Capacitively-coupled Pickupmentioning
confidence: 99%
“…At the same time, the bottom interior surface of the tile is coated by evaporation. The first step is evaporation of 10 nm of NiCr on the anode for capacitively coupling to exterior signal boards[58]. A second set of evaporation masks are used to deposit a metallic border overlapping the NiCr anode and connected to a copper pin, providing a charge drainage path to ground.…”
mentioning
confidence: 99%
“…In order to limit the number of the electronics channels but keep high time resolution, we develop a read-out scheme using transmission lines as presented in this publication. This read-out scheme is inspired by the approach developed in [19][20][21][22], but has substantial differences in the way we plan to use it. In references [19][20][21][22] the PMT is coupled to high yield scintillation crystal (LYSO, LSO), thus a large number of optical photons induce signals on all lines.…”
Section: Introductionmentioning
confidence: 99%
“…This read-out scheme is inspired by the approach developed in [19][20][21][22], but has substantial differences in the way we plan to use it. In references [19][20][21][22] the PMT is coupled to high yield scintillation crystal (LYSO, LSO), thus a large number of optical photons induce signals on all lines. In such configuration, it is not possible to distinguish signals from individual photons, but rather reconstruct the mean position of the induced signals along and across lines.…”
Section: Introductionmentioning
confidence: 99%
“…Second generation LAPPDs are also currently under active development by Incom Inc., with our university collaborators [8]. Most notable is a next generation design that incorporates an anode capacitively coupled through a thin metal film deposited onto the inside bottom of the detector, to an application specific printed circuit board, positioned beneath the detector tile, outside of the vacuum package.…”
Section: Introductionmentioning
confidence: 99%